Immune Response to Mycobacterium tuberculosis: A Narrative Review - de Martino, Maurizio; Lodi, Lorenzo; Galli, Luisa; Chiappini, Elena (Frontiers in Pediatrics, 2019)
The encounter between Mycobacterium tuberculosis (Mtb) and the host leads to a complex and multifaceted immune response possibly resulting in latent infection, tubercular disease or to the complete clearance of the pathogen. This narrative review summarizes the various immunologic mechanisms which modulate the individual ability to fight Mtb infection, focusing on the first phases of the infection. Mtb exhibits an extraordinary ability to subvert the defensive mechanisms of the macrophages. At the onset of the infection, Mtb is able to perforate the phagosome in the macrophage through the EsxA protein and, therefore, to block the maturation of the phagosome via nucleoside diphosphate kinase, and inhibits the lysosomal transport. With various mechanisms, some of which also operate at the level of macrophage DNA, the Mbt prevents the activation of defensive mechanisms toward the invading microorganism. Mtb is able to prevent the activation of the inflammasome, hindering the synthesis of IL-1and IL-18. Under normal conditions, IFN- stimulates the expression of MHC class II molecules on the macrophagesurface. However Mtb may suppress this mechanism thorugh the prolonged activation of TLR2. In conclusion, having to deal with a micro-organism of great evasive abilities, immune mechanisms have only one way to go: to focus on a very rapid response at the onset of the infection.